2020
DOI: 10.1002/ejp.1642
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ appraisals of injustice in the context of their child’s chronic pain: An interpretative phenomenological analysis

Abstract: Background: In line with research highlighting the role of observer appraisals in understanding individuals' pain experience, recent work has demonstrated the effects of parental child-and self-oriented injustice appraisals on child pain-related outcomes. However, research on parental injustice appraisals is in its infancy and lacks a valid and context-specific operationalization of what parental injustice appraisals of child pain precisely entail. The current study presents an in-depth qualitative analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Research has shown that higher levels of parental injustice appraisals are associated with increased parental stress and burden [31]. This may hinder parents' ability to effectively care for their child [32], highlighting the importance of healthcare professionals listening to parents and taking their experiences and expertise on board. As one participant stated, "nobody knows our child to the extent that we do" (Emma).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that higher levels of parental injustice appraisals are associated with increased parental stress and burden [31]. This may hinder parents' ability to effectively care for their child [32], highlighting the importance of healthcare professionals listening to parents and taking their experiences and expertise on board. As one participant stated, "nobody knows our child to the extent that we do" (Emma).…”
Section: Discussionmentioning
confidence: 99%
“…Parental tension and stress, which often occurs in the context of chronic or persistent child pain (Campo et al., 2007; Eccleston et al., 2004), may affect this. Furthermore, recent focus group research has demonstrated that mothers of children with chronic pain tend to frame the world as unfair; such framing may affect the way parents talk to their children about pain and further shape children's appraisal of pain (Baert et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, IPA is a bottom‐up‐oriented approach allowing the experiences of participants to speak for themselves, rather than fitting them into a predetermined categorical system (Pietkiewicz & Smith, 2014). IPA has been used successfully in the past to examine both lived chronic pain experiences (Osborn & Smith, 1998; Smith & Osborn, 2007) as well as the phenomenology of pain‐related injustice appraisals in adults (Baert et al, 2020; McParland, Eccleston, et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, as mentioned above, guidelines for recurrence were adopted to ensure the themes to reflect shared understandings. Rigor of the analyses was established further as the secondary author of the manuscript (FB), who has previous experience with conducting IPA (Baert et al, 2020), independently coded the first 10 pages of each of the focus group transcripts, serving as a check of the credibility of the analyses performed by the first author. Establishing that the coding by the primary author (FD) lined up with the coding of the initial sections by the secondary author, served as a form of quality control of the qualitative analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation